Hydromechanical modeling of unsaturated soils considering compaction effects on soil physical and hydraulic properties - Quevedo, R. (2024)
This study presents a methodology that includes hydraulic and mechanical constitutive relationships for modeling the complex volumetric behavior of unsaturated soils. The mechanical relationships are based on the generalized effective stress concept, and the hydraulic relationships adopt soil water retention curves dependent on soil deformation. After the formulation and the introduction of the governing equations, a study case based on the results of suction-controlled oedometric tests is presented, aiming for a better understanding of the effect of compaction on unsaturated soils. The oedometric compression curves of a first set of laboratory tests are reinterpreted in terms of the generalized effective stress concept to obtain the required model parameters. Then, numerical simulations are performed to analyze the soil susceptibility to large volumetric strains triggered by a combined effect of loading and wetting (collapse). The numerical simulations demonstrate that the proposed approach can model the collapse potential of soils with different compaction levels using a single set of parameters.